The effects of weather shocks on early childhood development - Diether W. Beuermann; Camilo Pecha; Juan Pedro Schmid (Inter-American Development Bank (IDB), 2017)
This study analyzes the effects of exposure to tropical storms and hurricanes during pregnancy on children's anthropometric measurements taken within the first five years of life. It combines destruction indexes at the district level with 13 yearly rounds of household level surveys from Jamaica. The empirical strategy exploits variation arising from the storms' timing and intensity across different cohorts within the same district. The findings suggest that when expectant mothers living in coastal-rural areas are affected by at least two hurricanes, their children are 56 percentage points more likely to show low birth weight. Furthermore, these children also experience negative impacts on anthropometric measurements taken within the first five years of life equivalent to 1.88 standard deviations in weight-for-age and 1.4 standard deviations in weight-for-height.
Keywords: I12; J13; O15; Q54; 330; Jamaica; anthropometric measurements; tropical storms